Ayenia grisea (Malvaceae-Byttnerioideae), a new species for Mexico and validation of Reevesia clarkii (Malvaceae/Helicteroideae) - Machuca Machuca, Karina (Instituto de Ecología, A.C., 2017)
Background and Aims: While performing the taxonomic treatment of the family Sterculiaceae for Flora del Bajío y de Regiones Adyacentes, a taxonomic novelty was disovered and a validation became necessary.Methods: A review of literature and specimens corresponding to the family Sterculiaceae of the herbaria ENCB, IEB, MEXU, QMEX was realized.Key results: A new species from Mexico is described and illustrated, Ayenia grisea belonging to section Leiayenia. The identity of Reevesia clarkii, an invalid name which has not been properly published, is validated and clarified.Conclusions: Both A. grisea and R. clarkii are endemic to Mexico and occur in the Bajío region.